2008
DOI: 10.1007/s10549-008-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

Population-based estimates of the relation between breast cancer risk, tumor subtype, and family history

Abstract: While a family history of breast cancer in first-degree relatives is an important risk factor for breast cancer, gathering information such as the age at diagnosis of affected relatives or information on second-degree relative history may be unnecessary in assessing personal breast cancer risk among women age >or=40 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…The association with family history of breast cancer has been similar across breast cancer subtypes,(3, 611, 40) stronger for ER+ breast cancer,(12, 41) and stronger for ER− or TN breast cancer. (13, 14, 42) The strongest evidence comes from a pooled analysis of 12 studies in the Breast Cancer Association Consortium, where an association with family history of breast cancer was present across subtypes, but with a stronger association for basal-like breast cancer.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The association with family history of breast cancer has been similar across breast cancer subtypes,(3, 611, 40) stronger for ER+ breast cancer,(12, 41) and stronger for ER− or TN breast cancer. (13, 14, 42) The strongest evidence comes from a pooled analysis of 12 studies in the Breast Cancer Association Consortium, where an association with family history of breast cancer was present across subtypes, but with a stronger association for basal-like breast cancer.…”
Section: Discussionmentioning
confidence: 92%
“…(1) Among African American women, estimates of the relative risk for first degree family history of breast cancer range from 1.65 to1.78,(2, 3) similar to findings from studies of European American and Asian women. (1, 4, 5) Among studies that reported results separately for estrogen receptor (ER) positive and ER− breast cancer, most reported similar associations by subtype,(3, 611) while one reported a stronger association with ER+ cancer(12) and two reported a stronger relation for ER− breast cancer. (13, 14) Only the Black Women’s Health Study reported on family history separately for ER+ and ER− breast cancer in African American women, with similar increases by subtype, but findings were based on small numbers.…”
Section: Introductionmentioning
confidence: 99%
“…We also did not consider the age at breast cancer diagnosis for relatives which can influence the breast cancer risk associated with family history (36). However, a recent population-based study suggested that the age of diagnosis of breast cancer in relatives does not substantially influence the risk of breast cancer associated with family history in women diagnosed over the age of 40 (48).…”
Section: Discussionmentioning
confidence: 99%
“…However, breast cancer in seconddegree relatives is reported with less accuracy than that in first-degree relatives (46), and is associated with lower risk of breast cancer than that in first-degree relatives (47,48). In one of the screening populations (NBSS) included in the present study, we have shown that compared with women with no family history, the relative risk of breast cancer for women with at least one affected first-degree was 1.44 (95% CI, 0.94-2.20) whereas for women with any first-or second-degree relative with breast cancer, the relative risk was only 1.14 (95% CI, 0.83-1.57; ref.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Furthermore, there have been many studies that compared epidemiological factors between tumor subtypes based on hormone receptor (HR) and HER2 status in the Western population [12][13][14][15][16][17][18][19] ; however, there has been only a few studies in the Asian population. 20,21 In this study, we describe the characteristics of breast cancer classified into tumor subtypes based on ER, PR and HER2 statuses and assess the heterogeneity in association with the epidemiological factors within tumor subtypes as evidence for the etiological differences between breast cancer subtypes through casecase analyses.…”
mentioning
confidence: 99%